Pluralistic Struggles in Gender, Sexuality and Coloniality Challenging Swedish Exceptionalism - Alm, Erika; Berg, Linda; Lundahl Hero, Mikela; Johansson, Anna; Laskar, Pia; Martinsson, Lena; Mulinari, Diana; Wasshede, Cathrin (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access book seeks to understand how politics is being made in a pluralistic sense, and explores how these political struggles are challenging and transforming gender, sexuality, and colonial norms. As researchers located in Sweden, a nation often cited as one of the most gender-equal and LGBTQ-tolerant nations, the contributions investigate political processes, decolonial struggles, and events beyond, nearby, and in between organizations, states, and national territories. The collection represents a variety of disciplines, and different theoretical conceptualizations of politics, feminist theory, and postcolonial and queer studies. Students and researchers with an interest of queer studies, gender studies, critical whiteness studies, and civil society studies will find this book an invaluable resource. .